A FRAMEWORK FOR SUCCESSFUL PROVISION OF SUSTAINABLE INFRASTRUCTURE WITH A PPP SCHEME IN INDONESIA - Marvyn Marvellino Gunawan; Andreas F.V. Roy (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
In the development of infrastructure projects with the PPP scheme, the government needs a way to assess the level of success and sustainability of related projects. This study will identify criteria that can be used to assess the success provision of sustainable infrastructure under the PPP scheme in Indonesia. After that, these criteria are arranged in a framework that will be tested against an infrastructure project. Analytic Network Proces (ANP) method is used to determine the ranking of each criterion so that a new development framework can be made and used in Indonesia. In this study, a questionnaire was developed which was distributed to four (4) experts in the field of infrastructure development in Indonesia. The results obtained are the framework for the success of providing sustainable infrastructure with the PPP scheme in Indonesia consists of 6 (six) success criteria with the percentage of involvement, which are Financial and Economy (30,47%), Law and Political (10,63%), Health Safety and Environmental (12,18%), Managerial and Technic (14,58%), Operational and Maintenance (16,70%), and Social and Stakeholder (15,44%). The six (6) success criteria are composed of twenty (20) derived sub-criteria. The PLTU Batang project which was chosen as the object of validation in this study did not meet 6 sub-criteria of the existing 20 sub-criteria. With this development framework, it can be taken into account in making decisions to determine the success of sustainable infrastructure projects with PPP schemes in Indonesia